2016
DOI: 10.1007/s00431-016-2821-8
|View full text |Cite
|
Sign up to set email alerts
|

Hospital clowning: a paediatrician’s view

Abstract: This study investigates the current position of hospital clowns from the perspective of paediatricians and paediatric residents. A total of 14 attending paediatricians and paediatric residents participated in two focus group sessions. Data were analysed using Atlas.ti 5.0. In general, physicians reported positive experiences regarding the interaction between hospital clowns and paediatric patients on the ward. Physicians were more interested in research on children’s perception of hospital clowns than in resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…Clowns, if they are to be an integral part of the health care system, must adjust their interventions according to hospital rules. Research conducted to evaluate the appreciation of clown interventions speaks in favor of integrating this practice into the hospital setting, as it is well received by patients, relatives, and hospital staff [30,31].…”
Section: Profession Of Therapeutic Clowningmentioning
confidence: 99%
“…Clowns, if they are to be an integral part of the health care system, must adjust their interventions according to hospital rules. Research conducted to evaluate the appreciation of clown interventions speaks in favor of integrating this practice into the hospital setting, as it is well received by patients, relatives, and hospital staff [30,31].…”
Section: Profession Of Therapeutic Clowningmentioning
confidence: 99%
“…As found by Blain et al (2012) and Van Venrooij and Barnhoorn (2017), the clown effect is enhanced by close collaboration and communication between medical clowns and healthcare professionals. In other countries, for instance Israel, medical clowns are involved in medical procedures, and they cooperate closely with hospital staff.…”
Section: Discussionmentioning
confidence: 69%
“…Studies have shown positive effects of these activities on the children, and it has been suggested that medical clowns should become an integral part of the health team (Kocherov et al, 2016; Ofir et al, 2016; Tener, Ofir, Lev-Wiesel, Franco, & On, 2016; Wolyniez et al, 2013). However, other studies showed a more negative attitude and suggested that the presence of clowns may interfere with medical routines and that children did not want a clown present during tests or medical procedures (Mansson et al, 2013; Vagnoli et al, 2005; Van Venrooij & Barnhoorn, 2017). In our study, most participants also did not support the idea of medical clowns being present during medical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings are very interesting, particularly in light of our recent study, which found that four out of 14 paediatricians and paediatric residents consider themselves afraid of clowns [5]. Meiri and colleagues advocate for more studies on this poorly described phenomenon, and we agree.…”
Section: Dear Editormentioning
confidence: 63%